If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13a + -13 = 14a + 5 Reorder the terms: -13 + 13a = 14a + 5 Reorder the terms: -13 + 13a = 5 + 14a Solving -13 + 13a = 5 + 14a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-14a' to each side of the equation. -13 + 13a + -14a = 5 + 14a + -14a Combine like terms: 13a + -14a = -1a -13 + -1a = 5 + 14a + -14a Combine like terms: 14a + -14a = 0 -13 + -1a = 5 + 0 -13 + -1a = 5 Add '13' to each side of the equation. -13 + 13 + -1a = 5 + 13 Combine like terms: -13 + 13 = 0 0 + -1a = 5 + 13 -1a = 5 + 13 Combine like terms: 5 + 13 = 18 -1a = 18 Divide each side by '-1'. a = -18 Simplifying a = -18
| -2m-7=-29 | | y=-1/4(-4)-6 | | 8x+13=53 | | 72=-8(r-2) | | a-b=7 | | 3.7x-8.5=13.7 | | y=-1/4(5)-6 | | 2x^2+27x-7.5=0 | | 6x-2=-32 | | 5=3(x-2)-(x-7) | | 2m+12=3m-21 | | -4a-5=-9 | | 2=(4x-2)(2-x) | | 3x^2+x-9=0 | | -2+4x=10 | | -3(x-4)=57 | | 2x(x+1)+x=1-2x^2 | | 5=-(-z+3) | | 7x-7=4x-7 | | 2(10+n)=48 | | (Y-6)-(y+7)=8y | | 7(p+7)-4(9+p)=12 | | 2.8p=11.2 | | -(x-8)=16 | | 102=-2+8n | | -2-6x=-74 | | 10+9m=55 | | 8z^2-8z+2=0 | | 3(5+a)=-9 | | 12(3x-3)=3(12x+6) | | -176=-8(x+9) | | -4(-2y-5)+5=97 |